(3EYdGe GdfHjg eeG RGO Ydi GdefgGL ef GdMGhj hGdHgLI hGdJfHjgs - (3CHj HcQ Hf hdj GdOjf Hf bGVj YLdhf GdTGaYj, Jbj GdOjf,J (B928 (3g` s
(3ChdgG (B:s
(3hHYO agPG JYdjb dWja CLeY ajg Ef TGA Gddg JYGdi eG ai GdJfHjg hGdMGhi hGdHgLI eeG dGjDNP ef GdefgGL s
(3BNQgG (B:s
(3hEf de jcf ef HGH GdMdGd hGdMQGe hGdaQGFV hGdSff Je GdcJGH s
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B104s
Keywords: (3Gdabg GdTGaYjs